2014
DOI: 10.1126/science.1259037
|View full text |Cite
|
Sign up to set email alerts
|

An oncogenic super-enhancer formed through somatic mutation of a noncoding intergenic element

Abstract: In certain human cancers, the expression of critical oncogenes is driven from large regulatory elements, called super-enhancers, which recruit much of the cell’s transcriptional apparatus and are defined by extensive acetylation of histone H3 lysine 27 (H3K27ac). In a subset of T-cell acute lymphoblastic leukemia (T-ALL) cases, we found that heterozygous somatic mutations are acquired that introduce binding motifs for the MYB transcription factor in a precise noncoding site, which creates a super-enhancer upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
726
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 705 publications
(761 citation statements)
references
References 48 publications
22
726
1
Order By: Relevance
“…Recently, a subset of T-ALL patients was found to harbor mutations near the oncogenic TAL1 locus that leads to establishment of a highly active SE via MYB binding (Mansour et al 2014). We observed enrichment of E/R-regulated RUNX1 binding sites in SEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a subset of T-ALL patients was found to harbor mutations near the oncogenic TAL1 locus that leads to establishment of a highly active SE via MYB binding (Mansour et al 2014). We observed enrichment of E/R-regulated RUNX1 binding sites in SEs.…”
Section: Discussionmentioning
confidence: 99%
“…They consist of enhancers with clustering of binding sites for multiple TFs and high histone K27 acetylation levels, reminiscent of locus control regions characterized at beta-globin or immune gene loci (Li et al 2002;Whyte et al 2013;Pott and Lieb 2014;Adam et al 2015). Recently, aberrant enhancer activity at the TAL1 gene locus was shown to drive leukemogenesis in T-ALL (Mansour et al 2014). However, the majority of cancer-relevant regulatory elements remain uncharacterized.…”
mentioning
confidence: 99%
“…14 A recent study has shown that an oncogenic super-enhancer forms through somatic mutation in a noncoding intergenic region and contributes to tumorigenesis in a subset of T cell acute lymphoblastic leukemia. 24 Additionally, enhancer activity has been linked to resistance to Notch inhibitor in T-cell leukemia. 25 Finally, emerging data suggests enhancer RNAs play a role in regulation of gene expression.…”
Section: Disruption Of Brd4 At the Putative C-myc Super-enhancer Regimentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Most ALL genomes harbor sequence and structural DNA alterations involving coding genes, as well as alterations of noncoding elements such as noncoding RNAs 23 and enhancer elements. 24,25 Here, we consider results from these studies in several categories: (1) identification of new subtypes of ALL that lack recurring gross chromosomal alterations; (2) characterization of the constellations of genetic alterations that define each ALL subtype; (3) the relationship between genetic alterations, clonal heterogeneity, and relapse; (4) identification of inherited genetic variants and mutations linked to ALL susceptibility and outcome; (5) and translating new discoveries to improved diagnostic, prognostic, and precision medicine approaches.…”
Section: Introductionmentioning
confidence: 99%
“…76 Another mechanism of leukemogenesis in T-ALL is mutations upstream of the T-ALL oncogene TAL1, which generate a binding site for the MYB transcription factor, thereby recruiting a protein complex including TAL1 and the H3K27 acetylator CREBBP, resulting in formation of an oncogenic "superenhancer" region characterized by high levels of H3K27 acetylation. 25 These examples underscore the importance of careful integrated analysis of coding and noncoding genomic, transcriptomic, and epigenomic features in ALL.…”
mentioning
confidence: 99%